PENINGKATAN HASIL BELAJAR TEMA KEGEMARANKU MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING - Sukmanasa, Elly; Damayanti, Danti (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2019)
The research with classroom action research approach is carried out in collaboration and cycles. It is conducted in class 1A Ciheuleut 2 Elementary School, Bogor Timur with the aims of describing learning outcomes level of success in Tema 2 Kegemaranku, Sub-tema 4 Gemar Membaca Pembelajaran ke 3 through scientific approach by applying discovery learning model. The subjects of this study are a teacher with 31 students in the odd semester 2018/2019 school year. The first cycle result showed that the average value of learning outcomes of the students who achieved completeness is 16 students (48%), while 15 students (32%) have not. Meanwhile, In the second cycle there are 27 students (87%) who achieved completeness, and 4 students (13%) have not yet achieved it yet. In the first cycle learning process, the students changing behavior values were 48% which was considered good enough, and in the second cycle the average score is 80% with good category. From the results of this study it can be concluded that the application of discovery learning in Tema 2 Kegemaranku, Subtema 4 Gemar Membaca, Pembelajaran 3 in class 1A Ciheuleut 2 Elementary School, Bogor Timur improves the changes of students behavior.